MODELISASI CAKE STAND DENGAN PENGGABUNGAN HASIL DEFORMASI TABUNG, PRISMA, DAN KURVA BEZIER - Nur Kholifah Ramadhani; Bagus Juliyanto; Firdaus Ubaidillah (UNEJ e-Proceeding, 2022)
A cake stand is a place for serving cakes to beautify the cake display. The cake stand consists of three parts: the base, the support, and the plate. This study developed a multilevel cake stand model by combining several geometric objects using the deformation method. Modeling the cake stands is divided into two stages. The first is to model the components of a cake stand by combining several geometric objects and Bezier curves. The geometric items used are tubes, rectangular prisms, and hexagonal prisms. Bezier curves used are curves of degrees two, three, four, and five. Second, combining the modeling results of each component of the cake stand on two types of cake stand modeling axes, namely one axis and three axes. This study produces 10,584 cake stand models on one modeling axis and three modeling axes. The cake stand model acquired can be visualized utilize Maple 18 software support on a computer. Keywords: Cake stand, Deformation method, Bezier curves, Modeling